Indigenous Cultural Safety Training for Applied Health, Social Work, and Education Professionals: A PRISMA Scoping Review - MacLean, Tammy L.; Qiang, Jinfan Rose; Henderson, Lynn; Bowra, Andrea; Howard, Lisa; Pringle, Victoria; Butsang, Tenzin; Rice, Emma; Di Ruggiero, Erica; Mashford-Pringle, Angela (International journal of environmental research and public health, 2023)
Anti-Indigenous racism is a widespread social problem in health and education systems in English-speaking colonized countries. Cultural safety training (CST) is often promoted as a key strategy to address this problem, yet little evidence exists on how CST is operationalized and evaluated in health and education systems. This scoping review sought to broadly synthesize the academic literature on how CST programs are developed, implemented, and evaluated in the applied health, social work and education fields in Canada, United States, Australia, and New Zealand. MEDLINE, EMBASE, CINAHL, ERIC, and ASSIA were searched for articles published between 1996 and 2020. The Joanna Briggs Institute’s three-step search strategy and PRISMA extension for scoping reviews were adopted, with 134 articles included. CST programs have grown significantly in the health, social work, and education fields in the last three decades, and they vary significantly in their objectives, modalities, timelines, and how they are evaluated. The involvement of Indigenous peoples in CST programs is common, but their roles are rarely specified. Indigenous groups must be intentionally and meaningfully engaged throughout the entire duration of research and practice. Cultural safety and various related concepts should be careful considered and applied for the relevant context.